Bioinspired Dual-Driven Binary Heterogeneous Nanofluidic Ionic Diodes - Wang, Lili (Langmuir : the ACS journal of surfaces and colloids, 2022)
Recently, bioinspired 2D material-based nanofluidic systems with unique properties and advantages have been receiving considerable research interest and getting rapid development. However, it remains a huge challenge to integrate adaptive responsiveness to external stimuli and asymmetric ion transport characteristics into the 2D nanofluidic systems. Herein, we report a dual-driven switchable asymmetric ionic transport phenomenon through a graphene oxide-based heterogeneous 2D nanofluidic membrane. Taking advantage of the formation of a charge heterojunction induced by the variation of pH or UV irradiation, a maximum ionic current rectification (ICR) ratio of ca. 56 for pH or 140 for light was achieved. Such smart nanofluidic devices with pH and light dual-responsiveness and asymmetric ion transport behaviors provide a universal strategy for potential applications in chemical sensing, water treatment, and energy conversion and establish a promising platform for exploring advanced quantum ionics biodevices with ultrafast signal transmission, nanochannel-structured bioreactors with high efficiency, etc